Age and gender differences in dimensions of the five-factor personality model - Marušić, Iris (Array, 1996)
The aim of this study was to examine age and gender differences in five broad personality dimensions as well as in their facets as defined by the NEO Personality Inventory - Revised (Costa and McCrae, 1992). Research was carried out on two samples of subjects. The first sample consisted of 466 high school graduates, 233 males and 233 females, whose mean age was 18. The second sample consisted of 256 adults, 123 males and 133 females, whose mean age was 46 years. Results were analysed using two-way ANOVA procedure, testing for gender and age main effects as well as for their interaction. Significant main effects for gender show that females score higher in neuroticism, openness to experience and agreeableness than their male counterparts. Main effects for age differences reveal that high school graduates are more neurotic, extraverted and open to experience, but less agreeable and conscientious than adult subjects. Interaction effect for extraversion shows that females are somewhat more extraversted than males at younger age, while in adults the difference is reversed. Furthermore, interaction of gender and age in agreeableness shows that in both age groups females are more agreeable, but the difference increases with age. Significant main effects and interactions both in domain and facet scales are discussed in terms of previous findings on gender and age differences in personality.